Liquid repellent nanocomposites obtained from one-step water-based spray1. Issue 24 (28th June 2015) - Milionis, A.; Dang, K.; Prato, M.; Loth, E.; Bayer, I. S.
<x xml:space="preserve">Abstract</x> A novel, single-step, environmentally-friendly, water-based, spray-coating approach to obtain superhydrophobic and superoleophobic nanocomposite coatings made from materials with low bioaccumulation.